Positron annihilation lifetime spectroscopy in nickel ferrite and iron oxide nanopowders - S M Asgarian; Z Kargar (Iranian Journal of Physics Research, 2019)
In this study, a positron annihilation lifetime spectrometer was set up and its resolution was optimized. The spectrometer is a fast-slow arrangement with time resolution of 250 ps. To obtain lifetime components and their intensities from analyzing positron annihilation lifetime spectrum, the Pascual software is used. Positrons are from a source of radioactive 22NaCl with 20 μCi activity enclosed in 7μm thick Mylar foil. The source correction to lifetime components and their intensities were carried out though measurements on defect-free Aluminum samples and Mylar foils. The positron annihilation lifetime spectrum in nickel ferrite and iron oxide nanopowders were measured. The shortest component was attributed to the annihilation of nonlocalized positrons in the samples. The intermediate lifetime is due to annihilation of positron in octahedral and tetrahedral cationic vacancies in the spinel structure and to annihilation of positrons in the surface of nanoparticles and vacancy clusters. The longest component is attributed to the annihilation of orthopositronium atoms formed in the large free volumes in the intergranular regions of the nanoparticles through ‘‘pick-off” process.